Employee Performance Factors Influenced By Work Motivation As Between From Incentives and Organizational Culture - Ika Puspa; Rosita Bangun; Anton anton; Martinus Tjendana; Dennis Wijaja (Institute of Computer Science (IOCS), 2021)
This study aims to explain that work motivation has an impact on the performance of employees who get incentives, both material and non-material incentives and good organizational culture. The type of research used in this research is explanatory research and the research method used is quantitative. The population in this study were employees of PT Angkasa Pura I Medan. The number of samples is 152 employees using the objective sampling technique. The data was processed using a computer program Lisrel 8.7. Based on the results of the analysis that work motivation increases when employees are given material and non-material incentives and supported by a good organizational culture, and with high employee motivation will affect employee performance. This is evident from the results of the inferential path analysis with the results of a significance value of F, which is 0.000 < 0.05 (alpha), the path coefficient value is 0.32 Material Incentives (X1), 0.44 Organizational Culture (X2) and Non-Material Incentives (X3). ) of 0.24 on Work Motivation (Z), the path coefficient value of 0.89 on Employee Performance (Y). This proves that the variables of Material Incentives, Organizational Culture and Non-Material Incentives have a significant influence on Work Motivation and Employee Performance either directly or indirectly.